Financing and the Challenges of Developing the Innovation Capacity of Enterprises in Developing Countries: The Case of the MENA Region and Africa - Mohamed Oudgou; Abdeslam Boudhar (Scientific Annals of Economics and Business)
Innovation currently represents a significant source of added value and competitiveness for companies on the international scale. However, financing innovation activities is a real challenge to overcome in order to successfully achieve the goals in emerging countries. The main objective of this paper is to conduct an empirical analysis on the identification of different sources of financing for firm innovation in the MENA region and Africa. To do this, we have constructed a battery of measures of the innovation capacity of firms: product, process, invention and innovation intensity of firms. In addition, the sources of financing were assessed by financing investments and working capital through bank debt, non-bank financial institutions, capital increase, equity, commercial debt and other sources of financing. The empirical study is based on the World Bank survey of more than 34,000 firms in the MENA region and Africa over the period 2011 and 2020. Through the use of several econometric modeling, the estimation results indicate the importance of bank financing, non-bank financial institutions, and trade credit in financing innovation of MENA and African firms.